The Safety and Efficacy of a Mixture of Honey, Olive Oil, and Beeswax for the Management of Hemorrhoids and Anal Fissure: A Pilot Study - Noori S. Al-Waili; Khelod S. Saloom; Thia N. Al-Waili; Ali N. Al-Waili (The Scientific World Journal)
We have found that a mixture of honey, olive oil, and beeswax was effective for treatment of diaper dermatitis, psoriasis, eczema, and skin fungal infection. The mixture has antibacterial properties. A prospective pilot study was conducted to evaluate the therapeutic effect of topical application of the mixture on patients with anal fissure or hemorrhoids.Fifteen consecutive patients, 13 males and 2 females, median age 45 years (range: 2870), who presented with anal fissure (5 patients) or first- to third-degree hemorrhoids (4 with first degree, 4 with second degree, and 2 with third degree), were treated with a 12-h application of a natural mixture containing honey, olive oil, and beeswax in ratio of 1:1:1(v/v/v). Bleeding, itching, edema, and erythema were measured using a scoring method: 0 = none, 1 = mild, 2 = moderate, 3 = severe, and 4 = very severe. The pain score was checked using a visual analog scale (minimum = 0, maximum = 10). Efficacy of treatment was assessed by comparing the symptoms' score before and after treatment; at weekly intervals for a maximum of 4 weeks. The patients were observed for evidence of any adverse effect such as appearance of new signs and symptoms, or worsening of the existing symptoms. The honey mixture significantly reduced bleeding and relieved itching in patients with hemorrhoids. Patients with anal fissure showed significant reduction in pain, bleeding, and itching after the treatment. No side effect was reported with use of the mixture. We conclude that a mixture of honey, olive oil, and beeswax is safe and clinically effective in the treatment of hemorrhoids and anal fissure, which paves the way for further randomized double blind studies.